Effects of Central Administration of Glutamine and Alanine on Feed Intake and Hypothalamic Expression of Orexigenic and Anorexigenic Neuropetides in Broiler Chicks - Khondowe Paul; Song-bo WANG; Sheng-feng CHEN; Jian-jian YU; Xiao-tong ZHU; Li-na WANG; Ping GAO; Qian-yun XI; Yong-liang ZHANG; Gang SHU; Qing-yan JIANG (Journal of Integrative Agriculture)
Different amino acids have been shown to affect feed intake when injected directly into the central nervous system of birds. In the present study, we investigated the effects of L-glutamine and L-alanine on feed intake and the mRNA expression levels of hypothalamic neuropeptides involved in feed intake regulation in broiler chicks. L-Glutamine or L-alanine was intra-cerebroventricularly (ICV) administered to 4-d-old broiler chicks and the feed intake were recorded at various time points. Quantitative PCR was performed to determine the hypothalamic mRNA expression levels of neuropeptide Y (NPY), agouti related protein (AgRP), pro-opiomelanocortin (POMC), melanocortin receptor 4 (MC4R) and corticotropin releasing factor (CRF). Our results showed that ICV administration of L-glutamine (0.55 or 5.5 μmol) significantly increased feed intake up to 2 h post-administration period and the hypothalamic NPY mRNA expression levels, while it markedly decreased hypothalamic POMC and CRF mRNA expression levels. In contrast, ICV administration of L-alanine (4 μmol) significantly decreased feed intake for the first 0.5 h post-administration period, and reduced the hypothalamic AgRP mRNA expression levels, while it remarkablely enhanced the mRNA expression levels of MC4R and CRF. These findings suggested that L-glutamine and L-alanine could act within the hypothalamus to influence feed intake in broiler chicks, and that both orexigenic and anorexigenic neuropeptide genes might contribute directly to these effects.